Pengaruh Penambahan Filler Al2O3 dan TiO2 pada Resin Polyester terhadap Sifat Fisik dan Mekanik - Ahmad Hasnul Fajri; Ilhamdi Ilhamdi; Ismet Hari Mulyadi; Jon Affi (Jurnal Teknik Mesin, 2023)
Polyester composites have been developed to have high strength and light density, but the fracture occurs due to very little plastic deformation or low strain values, pre-failure detection is difficult in these composites due to the rapid propagation of cracks in the composite system. To increase the strength and delay failure, the addition of filler in the form of Al2O3 and TiO2 particles is carried out. The use of particles as fillers in polymer composite materials is increasingly being developed. In this study, Al2O3 and TiO2 particles (0%, 2%, 4%, 6%, 8%, 10% vol.) were added in polyester matrix BQIN EX 157. by casting method; the liquid homogeneous mixture was carefully poured into a simple mould to be air dried. The composites were cut to serve as specimens for density test, mechanical tests such as tensile and compressive tests. The results showed a density of 1.23 g/cm3, a maximum strength of 47 MPa for 2% additional Al2O3 filler, (tensile, decreasing ̴11%) and 120 MPa (compressive) for a maximum of 2% additional Al2O3 (compressive, decreasing ̴3%) with TiO2 filler. The decrease in strength was caused by uneven particle dispersion, voids and agglomeration that occurred during the casting process.